2017
DOI: 10.1016/j.ijantimicag.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistant Enterobacteriaceae in the community: a scoping review

Abstract: Carbapenem antibiotics are used as a last resort to treat serious Gram-negative bacteria (GNB) infections, however carbapenemase-producing strains of GNB have emerged as a major source of resistance. Owing to the highly transmissible nature of plasmid-borne carbapenemases, numerous reports have warned about the likely spread into the community from healthcare settings. Since the prevalence of carbapenem-resistant Enterobacteriaceae (CRE) in the community is largely unknown, we conducted a scoping review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(168 citation statements)
references
References 47 publications
(120 reference statements)
8
154
0
6
Order By: Relevance
“…T he plasmid-mediated Klebsiella pneumoniae carbapenemase (KPC) emerged in the late 1990s and has become the predominant carbapenemase in clinical carbapenemresistant Enterobacteriaceae (CRE) isolates; these are primarily associated with the clonal dissemination of strains of K. pneumoniae, Enterobacter spp., and Escherichia coli (1,2). While health care-associated infections (HAI) comprise the majority of all cases involving CRE, community-associated infections (CAI) comprise up to 10.8% of CRE cases in the United States (3).…”
mentioning
confidence: 99%
“…T he plasmid-mediated Klebsiella pneumoniae carbapenemase (KPC) emerged in the late 1990s and has become the predominant carbapenemase in clinical carbapenemresistant Enterobacteriaceae (CRE) isolates; these are primarily associated with the clonal dissemination of strains of K. pneumoniae, Enterobacter spp., and Escherichia coli (1,2). While health care-associated infections (HAI) comprise the majority of all cases involving CRE, community-associated infections (CAI) comprise up to 10.8% of CRE cases in the United States (3).…”
mentioning
confidence: 99%
“…The spread of carbapenemase-producing gram-negative bacteria (GNB) in the community mimics the ESBL-PE pandemic [8]. A systematic review showed a rate of 5-10% in the USA, and up to 29.5% in one study from Taiwan.…”
Section: Emergence Of Resistant Bacteria Worldwide: a Need For Antibimentioning
confidence: 99%
“…2 In addition, a recent review of the literature demonstrated that according to US-based studies, the percentage of CPE isolates that could be associated with the community ranged from 5.6% to 10.8%. 3 We have recently demonstrated the less effective effect of fecal microbiota transplantation (FMT) on CPE compared to vancomycin-resistant Enterococci (VRE) fecal carriage. 4 Those results are consistent with another recent study 5 conducted in 6 patients colonized with CPE and showing an eradication of the colonization in only 2 of these 6 patients.…”
Section: Iterative Fecal Microbiota Transplantations For Eradicatingmentioning
confidence: 99%